Amphibians in danger : a worldwide warning - Fridell, Ron. (New York : Franklin Watts, 1999)
Describes the alarming worldwide disappearance of amphibians and its possible link to such conditions as erosion of the ozone layer, greenhouse effect and global warming, and environmental pollution.
Includes bibliographical references (p. 84-86) and index.
Booklist.
School Library Journal.
Wilson's Senior High School.
Young Adult
Keywords: Amphibians -- Monitoring -- Juvenile literature; Endangered species -- Juvenile literature; Amphibians; Endangered species; Amphibians; Endangered species